2020
DOI: 10.1136/esmoopen-2020-000763
|View full text |Cite
|
Sign up to set email alerts
|

Response assessment and outcome of combining immunotherapy and radiosurgery for brain metastasis from malignant melanoma

Abstract: BackgroundThe optimal sequence of stereotactic radiotherapy (SRT) and immune checkpoint inhibition (ICI) and assessment of response in patients with brain metastases from melanoma remain challenging.MethodsWe reviewed clinical and neuroimaging data of 62 patients with melanoma, including 26 patients with BRAF-mutant tumours, with newly diagnosed brain metastases treated with ICI alone (n=10, group 1), SRT alone or in combination with other systemic therapies (n=20, group 2) or ICI plus SRT (n=32, group 3). Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…The optimal timing of SRT in the multimodal therapeutic approach to BM from melanoma remains to be determined, although data from uncontrolled cohort studies also support early combination [82].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal timing of SRT in the multimodal therapeutic approach to BM from melanoma remains to be determined, although data from uncontrolled cohort studies also support early combination [82].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The rate of pseudoprogression with immunotherapy alone appears to be low. Further studies are required to determine how to distinguish treatment-related changes from progression after SRT with or without systemic therapy [82]. For BM patients, whose primary tumour is still unknown after a first work-up at diagnosis, whole-body FDG-PET in the follow-up may be useful.…”
Section: Monitoring and Follow-upmentioning
confidence: 99%
“… 21 In two case series comprising 68 patients with metastatic melanoma who received ICI and radiotherapy (36, 32 patients respectively), no evidence of abscopal effects were found (total n = 61, 62). 19 , 20 …”
Section: Resultsmentioning
confidence: 99%
“… 21 , 22 This is contradicted, however by two studies which found no evidence of the abscopal effect; conclusions from one of these studies, however, is limited as reduction in tumor size was primarily studied for CNS metastases which may be a significantly rarer phenomenon. 20 In addition, in one case report a patient experienced an initial abscopal effect (following irradiation of brain metastases) and subsequent progression of extracranial disease, with a second abscopal effect observed following irradiation of a spinal metastasis. 17 This suggests that there are systematic changes occurring which promote anti-tumor immunity and may be harnessed in future treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Further guidance on endpoints in immunotherapy trials in BM—particularly the issue of separating out the intracranial and extracranial response—has been provided by the FDA ( 20 ). Whilst criteria are dynamic ( 21 , 22 ), such guidance should reduce the over-reporting of progressive disease due to imaging immune responses and consensus guidelines—which are technically low-quality evidence—will invariably will be applied in trials going forward ( 23 ).…”
Section: Conventional Mri Biomarkers Of Early Treatment Responsementioning
confidence: 99%